Client Perceptions of the Most and Least Helpful Aspects of Couple Therapy. Issue 3 (3rd July 2022) - Eldridge, Kathleen; Mason, Jessica; Christensen, Andrew
Abstract: Couples have a unique perspective to share about the therapy they receive. The current study uses a mixed-methods design to examine what couples report about most and least helpful elements of two behaviorally-based treatments tested in a large clinical trial of couple therapy. Results indicate that responses are highly variable and fall into five main themes, which are then compared between treatment conditions, genders, and outcome groups. One interesting finding is that all groups reported wanting more discussion of sexual issues. Findings are discussed in the context of common factors research, recent developments toward unified principles of change in couple therapy, and model-specific differences.